Starting a Community Garden - Eva C. Worden; Adrian Hunsberger; John McLaughlin (EDIS, 2004)
A community garden is a collaborative greenspace in which the participants share in both the maintenance and the rewards. There is a long tradition of community gardening in various parts of the United States and around the world. This publication has been developed to assist those who wish to form a community garden in Florida. This document is ENH 966, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 28, 2002. Reviewed: October 2003.